2020
DOI: 10.1053/j.ajkd.2020.06.009
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19–Related Collapsing Glomerulopathy in a Kidney Transplant Recipient

Abstract: We report a case of a kidney transplant recipient who presented with acute kidney injury and nephrotic-range proteinuria in a context of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Kidney biopsy revealed collapsing glomerulopathy. Droplet-based digital polymerase chain reaction did not detect the presence of SARS-CoV-2 RNA in the biopsy fragment, and the virus was barely detectable in plasma at the time of the biopsy. SARS-CoV-2 RNAemia peaked several days later, followed by a seroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 18 publications
2
56
0
3
Order By: Relevance
“…His renal biopsy findings support the diagnosis of CG concomitant with oxalate nephropathy because of high dosage of vitamin C. The APOL-1 risk variants expressed heterozygous of wild type and G1 variants, which are regarded as low-risks for CG. These case reports suggested that CG might be promoted by COVID-19 even in the presence of a low-risk APOL1 genotype (3,19). Previous studies have shown that the APOL1 risk alleles are related to an increased proportion of newly diagnosed CG.…”
Section: High-risk Apol1 Genotype and Covid-19-associated Collapsingmentioning
confidence: 83%
See 2 more Smart Citations
“…His renal biopsy findings support the diagnosis of CG concomitant with oxalate nephropathy because of high dosage of vitamin C. The APOL-1 risk variants expressed heterozygous of wild type and G1 variants, which are regarded as low-risks for CG. These case reports suggested that CG might be promoted by COVID-19 even in the presence of a low-risk APOL1 genotype (3,19). Previous studies have shown that the APOL1 risk alleles are related to an increased proportion of newly diagnosed CG.…”
Section: High-risk Apol1 Genotype and Covid-19-associated Collapsingmentioning
confidence: 83%
“…Studies have also shown that baseline chronic kidney disease (CKD) or pre-existing acute renal impairment is associated with increased mortality (4,9). Renal tropism of this virus was detected by viral RNA in various renal structures of individuals who died from SARS-CoV-2, inclusive of glomeruli (3). In a more recent meta-analysis of five relevant studies and 964 COVID-19 positive patients, the cumula tive event rate of acute renal failure was 7.1% (95% confidence interval [CI]: 1.8%-24.5%, P<0.001, I 2 = 92.4) (10).…”
Section: Acute Kidney Injury In Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, case reports of patients with African background with AKI, nephrotic proteinuria, and a histopathological picture of collapsing glomerulopathy have been published. 33,[40][41][42][43][44][45][46] The majority of the patients had an apolipoprotein L1 (APOL1) high-risk genotype, [40][41][42][43] which also cannot be excluded for the patients who did not perform a genetic investigation. 33,[43][44][45] Patients with the G1 and G2 alleles of the APOL1 gene, in their vast majority of Sub-Saharan African descent, are known to be susceptible to chronic kidney disease and glomerulopathies such as focal segmental glomerulosclerosis and HIVassociated nephropathy.…”
Section: Uponmentioning
confidence: 99%
“…Lazareth et al 46 have reported a case of collapsing glomerulopathy in a kidney transplant recipient of Sub-Saharan African origin, as well as SARS-CoV-2 infection with a low-risk donor of APOL1 genotype G0/G2, where the genotype of the recipient was G0/G0. This case report illustrates that a high-risk APOL1 donor background is not a prerequisite for severe podocyte injury to occur in kidney allografts in the context of SARS-CoV-2.…”
Section: Uponmentioning
confidence: 99%